The Development of Green Transformational Leadership: A Bibliometric Analysis - Rumijati, Aniek; Novianti, Khusnul Rofida (MEC-J (Management and Economics Journal), 2024)
The latest development in the field of global leadership studies is green transformational leadership (GTL) which combines the ideas of transformational leadership with a focus on ecological responsibility and environmental sustainability. This research aims to determine the development of the concept of green leadership, especially green transformational leadership in leadership studies literature using bibliometric analysis. Data was obtained from the Scopus journal database using 187 articles published in the academic journal from 2009 to 2024 and analyzed using VOSviewer software to conduct co-authorship, co-occurrence, and citation analysis. Furthermore, the identification of dominant themes was also carried out to highlight important topics in the concept of green transformational leadership. The importance of this research lies in finding study ideas related to green transformational leadership which can help in developing a conceptual framework for future research related to the concept of sustainability in leadership research.